2000
DOI: 10.1007/s004010000230
|View full text |Cite
|
Sign up to set email alerts
|

The developmental and aging changes of Down's syndrome cell adhesion molecule expression in normal and Down's syndrome brains

Abstract: We studied the expression of Down's syndrome cell adhesion molecule (DSCAM) in Down's syndrome (DS) and control brains, using antisera against peptide fragments of DSCAM. On Western blots of human, mouse and rat brain homogenates, the antisera recognized a product at approximately 200 kDa. In the brain of a 2-year-old patient with DS, Western blotting revealed an overexpression of DSCAM compared to an age-matched control. Immunohistochemistry demonstrated DSCAM in the cerebral and cerebellar white matter of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…Increased DSCAM protein levels in the brains of DS patients have been reported (Saito et al, 2000). We observed that overexpression of DSCAM in hippocampal neurons produced a dramatic inhibition of dendrite branching, in agreement with the dendritic phenotype observed in DS patients (Marin-Padilla, 1972).…”
Section: Discussionsupporting
confidence: 89%
“…Increased DSCAM protein levels in the brains of DS patients have been reported (Saito et al, 2000). We observed that overexpression of DSCAM in hippocampal neurons produced a dramatic inhibition of dendrite branching, in agreement with the dendritic phenotype observed in DS patients (Marin-Padilla, 1972).…”
Section: Discussionsupporting
confidence: 89%
“…4). This expression pattern, which is very similar to that described for DSCAM in the human adult brain using immunohistochemistry (Saito et al, 2000), is of significance as these regions of the brain are involved in the input and processing of somatosensory information, spatial and explicit learning and memory, and the learning of motor skills (Kandel et al, 1995). Moreover, the cortex, hippocampus and cerebellum are particularly affected in DS (Becker et al, 1993;Jernigan et al, 1993;Golden and Hyman, 1994).…”
Section: Pattern Of Dscam Expression In the Adult Brainsupporting
confidence: 66%
“…Compared with the normal subjects, the patients with DS have increased cerebral expression of DSCAM protein because of the trisomy of chromosome 21. Elevated levels of DSCAM protein may lead to abnormal lamination and gross architecture through alterations of the adhesive properties of neurons (Agarwala et al, 2000;Saito et al, 2000). Given the homology of DSCAM to cell adhesion molecules involved in development and synaptic plasticity, we speculated that Dscam gene to be the best candidate for a putative signal in affecting SGZ progenitor cell fate.…”
Section: Figurementioning
confidence: 99%